Engaging boys as "Structured Allies" to prevent gender-based violence against girls: Results from the CARE Tipping Point Initiative in Nepal. - Kathryn M Yount; Robert Durr; Suniti Neogy; Yuk Fai Cheong (PLoS ONE)
Global efforts to end violence against women and girls (VAWG) include engaging men and boys. The CARE Tipping Point Initiative in Nepal engaged men and boys as structured allies in girl-centered movement building to prevent VAWG, including sexual bullying and gender harassment (SBGH). We assessed whether this initiative in Kapilvastu and Rupandehi districts in Western Nepal affected adolescent boys' reports of ever witnessing SBGH of a girl by another boy. Eligible boys were unmarried, 12-16 years, and not intending to migrate over the next 24 months. 1,154 (93% of) eligible, consenting boys across 54 randomly selected clusters participated at baseline, and 1,143 (99.0% of) baseline participants were followed. Outcomes were ever witnessed acts of non-contact (0-7; 0/1) and contact (0-7; 0/1) SBGH of a girl by another boy or male peer. Difference-in-difference (DID) regressions were estimated to assess the unadjusted and adjusted average treatment effects on these outcomes for participants assigned to the Tipping Point Program (TPP), Tipping Point Plus Program (TPP+), or control. Reports of ever witnessing acts of non-contact SBGH increased from 64% at baseline to 77% at follow-up due to increased reporting of ever witnessing "writing sexual messages…about a girl." In adjusted models, boys in the TPP+ group ever witnessed 0.42 fewer acts of non-contact SBGH than did boys in the control group. Reports of ever witnessing acts of contact SBGH implausibly declined from 42% at baseline to 38% at follow-up, and this trend did not differ across study arm in adjusted models. Thus, compared to the control group, the TPP+ group may have reported smaller increases in ever witnessing acts of non-contact SBGH and more often concealed previously reported acts of non-contact SBGH ever witnessed. Future intervention studies should assess bystander motivation, self-efficacy, and behavior as direct measures of boys' allyship to prevent SBGH and VAWG.